Zinc deficits, mucositis, and mucosal macrophage perturbation: is there a relationship?. Issue 5 (September 2019) - Thomsen, Michael; Vitetta, Luis
Abstract : Purpose of review: Mucositis is a common and therapy-limiting adverse effect of cancer treatments including radiotherapy, chemotherapy, and immunotherapy. The optimal zinc formulation, dosage, and timing of administration warrant further research as does the efficacious prevention of febrile mucositis that predisposes to febrile neutropenia. Recent findings: Metaanalyses concluded that zinc sulfate failed to significantly reduce the incidence or severity of chemotherapy-induced oral mucositis, whereas polaprezinc was associated with a significant reduction. Three new trials were published in 2018. The first trial found that zinc sulfate reduced the incidence and severity of chemotherapy-induced oral mucositis. The second reported that polaprezinc reduced oral mucositis in pediatric patients receiving high-dose chemotherapy for hematopoietic stem cell transplantation. The third trial demonstrated efficacy for a zinc lozenge for postoperative sore throat induced by an endotracheal intubation. Summary: Zinc deficits, dietary or induced by cancer, are common in patients with cancer. Febrile mucositis may better describe the condition linking mucositis with febrile neutropenia. Febrile mucositis disrupts treatment and may be life-threatening. A paradigm shift is needed for a more comprehensive understanding of febrile mucositis. Zinc effects on the thymic immunological network and T lymphocytes during chemoradiotherapy regimens also warrant further investigation.